Unveiling the Signature of Halal Leather: A Comparative Study of Surface Morphology, Functional Groups and Thermal Characteristics - Syabani, Muh Wahyu; Iswahyuni, Iswahyuni; Warmiati, Warmiati; Prayitno, Kutut Aji; Saraswati, Henny; Hernandha, Rahmandhika Firdauzha Hary (Indonesian Journal of Halal Research, 2023)
The halal certification of products holds significant importance for Muslim consumers, necessitating the development of reliable techniques for identifying leather products made from raw materials. This study employed rapid and accurate analytical methods to distinguish between cowhide, pigskin, and artificial leather. A combination of scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), and differential scanning calorimetry (DSC) was used to assess the variations in collagen fiber structures and thermal stability among the leather samples. The findings revealed that morphological surface analysis, including grain patterns and pores, facilitated swift differentiation between different leather types. Pigskins exhibit three-hole patterns on their morphological surface compared to cowhide, with random pores and tighter grain patterns, whereas artificial leather lacks natural grain patterns and pores altogether. While FTIR spectra exhibited similarities between cowhide and pigskin leathers, variations in vibration intensity enabled effective discrimination. Artificial leather, particularly PVC-based materials, displayed distinct spectra, allowing FTIR spectroscopy to effectively discern between halal and non-halal leather. Cowhide possesses strong and sharp vibration at wavenumber 1736, 1277, and 817 cm-1 compared to pigskin, which has stronger vibration at 1534 cm-1. Meanwhile, PVC-based artificial leather exhibited stretching at 1723 and 744 cm-1 wavenumbers. DSC analysis proved valuable in differentiating between genuine and artificial leather based on unique peaks and thermal behavior. These three techniques provide reliable means to determine the raw material origins of leather products.